Expedient Method for Samarium(II) Iodide Preparation Utilizing a Flow Approach - Voltrova, Svatava; Srogl, Jiri (Synlett, 2013)
A facile method of SmI2 preparation is presented which utilizes a continuous-flow system. The notoriously cumbersome handling and storage of the reagent can thus be avoided as appropriate amounts of SmI2 can be conveniently prepared when needed. The method is illustrated and the reagent quality demonstrated by a series of typical SmI2-induced transformations.
Keywords: flow; samarium; samarium(II) iodide; reduction; reductive coupling